2018
DOI: 10.1103/physrevb.98.195305
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional transport in low-density two-dimensional Rashba systems

Abstract: Rashba spin-orbit coupling appears in 2D systems lacking inversion symmetry, and causes the spinsplitting of otherwise degenerate energy bands into an upper and lower helicity band. In this paper, we explore how impurity scattering affects transport in the ultra-low density regime where electrons are confined to the lower helicity band. A previous study has investigated the conductivity in this regime using a treatment in the first Born approximation. In this work, we use the full T -matrix to uncover new feat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…The corresponding current density is given by Eq. (12) with v µ , p ±µ , and Φ ±µ taken (20) and has the temperature dependence T 4 ln |E F /T |. A similar temperature dependence was recently obtained for the relaxation rate of higher-order odd angular harmonics of electron distribution in 2D systems with parabolic spectrum due to electron-electron collisions.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…The corresponding current density is given by Eq. (12) with v µ , p ±µ , and Φ ±µ taken (20) and has the temperature dependence T 4 ln |E F /T |. A similar temperature dependence was recently obtained for the relaxation rate of higher-order odd angular harmonics of electron distribution in 2D systems with parabolic spectrum due to electron-electron collisions.…”
supporting
confidence: 73%
“…This equation is easily solved for C ee µ and the correction to the current is calculated using Eq. (12). Below the Dirac point, it equals…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from this, they possess a nontrivial structure of energy bands, which makes their charge-and heattransport properties an interesting subject of research. So far, the main attention was focused on 2D SOC systems with purely elastic scattering [2][3][4][5][6] . In particular, it was found that the impurity-related resistivity exhibits an unconventional dependence on the electron density 2,4 .…”
Section: Introductionmentioning
confidence: 99%
“…So far, the main attention was focused on 2D SOC systems with purely elastic scattering [2][3][4][5][6] . In particular, it was found that the impurity-related resistivity exhibits an unconventional dependence on the electron density 2,4 . Far less attention was given to the effects of inelastic scattering.…”
Section: Introductionmentioning
confidence: 99%